COMICS AS AN INTERESTING INDONESIAN LANGUAGE LEARNING MEDIA FOR SD/MI STUDENTS - Ridzal, Diana Falhabibah Saifur; Mislikhah, St.; Mu’alimin, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2023)
Abstract Comics are a series of images created as a learning medium for conveying information. Comic teaching materials are tools used by teachers or instructors in the teaching-learning process to convey information through pictures following stories. The main purpose of this research was to analyze comics as an interesting medium for learning Indonesian Language in elementary school (SD/MI) students. The research method used was library research. The data sources in this research were previous research findings from both national and international journals. The literature reviews were based on existing literature and documentation data. Data analysis from the results of literature and research using qualitative analysis started with data reduction, display, conclusion, and data verification. The research results showed that the use of comics as a learning medium was very suitable for helping students, especially SD/MI students, to understand and achieve the goals of learning Indonesian language. However, it needs to prepare teaching materials in comic form. The images in comics must be arranged carefully so as not to make information overwhelm students' imaginations. Various images in comics help students gain an understanding of the objectives to be achieved in the subject. Therefore, learning media in the form of comics can be used as an alternative to Indonesian language learning process for elementary students.